Correlation between low level of vitamin D [25(OH)D] and high level of interleukin-2 (IL-2) in preterm birth: a systematic review - Sanjaya, I Nyoman Hariyasa Sanjaya; Mulayana, Ryan Saktika Mulyana; I Gusti Ngurah Agung Trisnu Kamajaya (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2024)
Preterm birth, characterized by uterine contractions and cervical changes before 37 weeks of gestation, is a leading cause of neonatal morbidity and mortality worldwide. Its multifactorial pathophysiological mechanisms include inflammatory responses. Emerging evidence suggests that vitamin D and interleukin-2 (IL-2), a pro-inflammatory cytokine, play significant roles in preterm birth by modulating immune responses. A systematic literature review was conducted using Google Scholar and PUBMED databases (2010–2023). Keywords included